Bridging geometry and cultures for junior high school level: Rumoh Aceh design from a computational thinking perspective - Azmi, Nur; Arif, Salmawaty; Sofyan, Hizir; Oktavia, Rini (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
Recent discourse in mathematics education emphasizes the need for culturally relevant pedagogy and the integration of higher-order thinking skills, yet limited research explores the intersection of ethnomathematics and computational thinking within school curricula. This study addresses this gap by proposing a novel instructional framework that incorporates computational thinking into the ethnomathematical exploration of Rumoh Aceh—a traditional Acehnese house—within the context of junior high school geometry education in Indonesia. The research aims to enhance students’ understanding of geometric concepts such as lines, angles, shapes, and spatial structures through culturally grounded learning experiences. Using the four core components of computational thinking—decomposition, abstraction, pattern recognition, and algorithmic thinking—the geometric design of Rumoh Aceh is analyzed to reveal its mathematical significance. Data collection was conducted through ethnographic methods, including observation, interviews with local experts, and documentation analysis. The findings demonstrate that applying computational thinking to cultural artifacts fosters students’ ability to recognize geometric patterns, simplify complex problems, and develop structured problem-solving strategies. Furthermore, the integration of cultural context enriches students’ appreciation of their heritage while cultivating critical thinking and mathematical reasoning. This study provides empirical evidence supporting the pedagogical value of merging ethnomathematics with computational thinking, offering a meaningful and culturally responsive approach to mathematics education.